Amor, singeleza e duração: sobre um poema de Peter Handke - Laura Moosburger (O Que Nos Faz Pensar)
This paper explores, in the Poem to Duration [Gedicht an die Dauer] by Peter Handke, the essential relation between love and singularity in the horizon of duration – chosen by the poet in reference to Bergson’s philosophy –, and tries to show how the experience of love, inextricable of the singularity that is the mark of duration, of time unavoidably lived, is an experience of “singeleza” – Portuguese word which, as we understand it here, points to a poetic sensibility invested of  such a tenderness capable of capturing the irreductible singular, fragile, fleeting, personal and intimate.